2016
DOI: 10.1074/jbc.m115.696831
|View full text |Cite|
|
Sign up to set email alerts
|

The Tumor-suppressive Small GTPase DiRas1 Binds the Noncanonical Guanine Nucleotide Exchange Factor SmgGDS and Antagonizes SmgGDS Interactions with Oncogenic Small GTPases

Abstract: The small GTPase DiRas1 has tumor-suppressive activities, unlike the oncogenic properties more common to small GTPases such as K-Ras and RhoA. Although DiRas1 has been found to be a tumor suppressor in gliomas and esophageal squamous cell carcinomas, the mechanisms by which it inhibits malignant phenotypes have not been fully determined. In this study, we demonstrate that DiRas1 binds to SmgGDS, a protein that promotes the activation of several oncogenic GTPases. In silico docking studies predict that DiRas1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
(72 reference statements)
1
38
0
Order By: Relevance
“…DIRAS1 has been suggested as a tumor suppresser in several human cancers, including colorectal cancer, 9 esophageal squamous cell carcinoma, 5 and glioma 6 . The mechanism underlying these tumor-suppressive activities might contribute to its ability to bind to SmgGDS, a protein that induces the activation of several oncogenic GTPases 18 . The ERK1/2, p38 mitogen-activated protein kinase (MAPK), and nuclear factor κB (NF-κB) pathways can be inhibited by the restoration of DIRAS1 expression 5, 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIRAS1 has been suggested as a tumor suppresser in several human cancers, including colorectal cancer, 9 esophageal squamous cell carcinoma, 5 and glioma 6 . The mechanism underlying these tumor-suppressive activities might contribute to its ability to bind to SmgGDS, a protein that induces the activation of several oncogenic GTPases 18 . The ERK1/2, p38 mitogen-activated protein kinase (MAPK), and nuclear factor κB (NF-κB) pathways can be inhibited by the restoration of DIRAS1 expression 5, 18.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying these tumor-suppressive activities might contribute to its ability to bind to SmgGDS, a protein that induces the activation of several oncogenic GTPases 18 . The ERK1/2, p38 mitogen-activated protein kinase (MAPK), and nuclear factor κB (NF-κB) pathways can be inhibited by the restoration of DIRAS1 expression 5, 18. Studies have indicated that downregulation of DIRAS1 is attributed to DNA copy number loss, LOH, and hypermethylation 5, 9.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of DIRAS1 in mammals is poorly characterized. DIRAS1 has been suggested to function as a tumor suppressor in glioblastoma and other tumor cell lines through the inhibition of Ras-mediated transformation, altered NF-κB transcription activity, diminished ERK1/2 and MAPK signaling, and antagonization of pro-oncogenic small Ras GTPases (44). Studies in C. elegans have demonstrated that the DIRAS1 and exchange protein directly activated by cAMP (EPAC) orthologs colocalize at the presynaptic membranes and are needed for the maintenance of normal presynaptic acetylcholine release at neuromuscular junctions (17).…”
Section: Discussionmentioning
confidence: 99%
“…SmgGDS also acts as a chaperone protein for small GTPases having a CaaX motif, in addition to a GEF for Rho family proteins (5)(6)(7)(8)(9)(10). SmgGDS interacts with various small GTPases possessing a Cterminal polybasic region (PBR) upstream of the CaaX motif in a hypervariable region (HVR) (5,6,(11)(12)(13). SmgGDS is overexpressed in nonsmall cell lung carcinoma (14,15), prostate cancer (16), breast cancer (15,17), and pancreatic cancer (15).…”
mentioning
confidence: 99%